2015
DOI: 10.1016/j.polymer.2015.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxations of Acrylic-Polyurethane hybrid materials

Abstract: In this work we present a dielectric relaxation study of Acrilyc/Polyurethane polymers synthesized via miniemulsion photo-polymerization. Three different samples, both parts of the synthesized hybrid latex (SOL and GEL fractions) and a full acrylic sample as reference have been considered. Besides dielectric experiments using broadband Dielectric Spectroscopy (BDS) technique, complementary Differential Scanning Calorimetry measurements have been performed. The thermodynamic characterization outcomes evidence v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In order to understand the differences exhibited by the network relaxation it is useful to recall the molecular interpretation obtained for the dielectric relaxation of these polymers. It was previously reported [10] that Acrylic-PU samples present mainly three different dielectric relaxations, the α-relaxation, the dangling chain relaxation and the network relaxation. The dipolar entities responsible for the α-relaxation were attributed to segments of the acrylic main chains.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In order to understand the differences exhibited by the network relaxation it is useful to recall the molecular interpretation obtained for the dielectric relaxation of these polymers. It was previously reported [10] that Acrylic-PU samples present mainly three different dielectric relaxations, the α-relaxation, the dangling chain relaxation and the network relaxation. The dipolar entities responsible for the α-relaxation were attributed to segments of the acrylic main chains.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, the network relaxation process was reported to be originated by the presence of orientationally correlated urethane-segment bundles belonging to PU chains linked by both ends to the acrylic main chain and forming the gel network. The presence of such large molecular entities responsible for the relaxation phenomena was inferred by the high values of both the dielectric strength and the limiting high temperature relaxation time [10]. Now, when comparing the values of τ max obtained for the network relaxation in the three gel samples at 400 K, we see that Gel A and Gel C show both values close to 5 ms and that τ max is nearly a factor of 5 smaller for Gel B (see Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 The electrical properties of polyurethanes and poly(urethane-urea) are important and are studied in order to obtain intelligent polymeric materials with electrical properties determined by the frequency and intensity of the applied electric field. 7,41 Previous results 42,43 have indicated that the dielectric constant and the dissipation factor of the polyurethanes are dependent both on the orientation of the dipole of the hard and soft segments, but also on their microstructure. Dielectric spectroscopy is used for the investigation of the molecular dynamics of the polyurethanes and poly(urethane-urea) with polar structure in very broad range of frequencies.…”
Section: Introductionmentioning
confidence: 99%